A Meta-Analysis of the Review Literature on Multiple-Criteria Decision Aids for Environmental Issues - Panagiota Digkoglou; Alexis Tsoukiàs; Jason Papathanasiou; Katerina Gotzamani (Applied Sciences)
Environmental decision making is a complex process that requires the consideration of multiple factors. Therefore, Multiple-Criteria Decision Aiding (MCDA) aims to address the challenges of environmental decision making. This paper analyses published review papers that discuss the use of MCDA in environmental problems, with the goal of drawing useful meta-level conclusions. The review papers were categorised by application field and sorted by various criteria. The main findings of each paper were also analysed. The analysis reveals that MCDA publications in the specific domain have shown a strong upward trend. Hybrid MCDA is increasingly being applied as it can cope with the multidimensional challenges of environmental decision making. AHP appears to be the most widespread method. The sustainable energy sector is particularly interested in the use of MCDA. However, while decision-makers extensively use MCDA in environmental problems, its corresponding application in real-world settings is not always satisfactory.